Modelling business processes using evolutionary generated petri nets - Plucar, J. (EAI, 2017)
Evolutionary algorithms or computations (EC) are commonly used for solving problems such as optimization and reverse engineering of complex systems. In this paper, we present bio-inspired approach in a process of evolving design for the workflow processes. Workflow management systems often offer modelling capabilities to support construction of business processes. However, constructing formal workflow model for the extensive business process is a non-trivial task. Workflow process could be described as bipartite graph and therefore interpreted by Petri Nets. The goal is to describe a process for evolving and verification of petri nets.